INVESTIGATING COMPENSATORY STRATEGIES IN YOUNG LEARNERS WITH MILD ADHD IN SECOND LANGUAGE ACQUISITION - Kadek Jessica Ogilvy; Sylvia (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
ABSTRACT This study explores the use of compensatory strategies by junior high school students with mild Attention-Deficit/Hyperactivity Disorder (ADHD) in the process of Second Language Acquisition (SLA). The primary focus of this research is to identify how executive function difficulties, particularly sustained attention and working memory, affect language fluency. Using a qualitative approach through case studies and task analysis, this study observes learners’ interactions when dealing with complex texts and communicative tasks.The preliminary findings indicate that learners with mild ADHD unconsciously develop unique compensatory mechanisms, such as intensive use of visual aids, breaking tasks into micro-units (micro-tasking), and utilizing Artificial Intelligence (AI) technology as an external cognitive regulator. However, these strategies often conflict with traditional language teaching methods that tend to be linear in nature. The critical analysis in this study emphasizes the importance of differentiated instruction and more flexible Task-Based Language Teaching (TBLT) approaches. The findings are expected to contribute to the development of more inclusive and neurodiversity-friendly syllabi, as well as provide practical guidance for language teachers in facilitating independent and effective learning strategies for learners with attention-related challenges.   ABSTRAK Penelitian ini mengeksplorasi penggunaan strategi kompensatori oleh siswa Sekolah Menengah Pertama dengan Attention-Deficit/Hyperactivity Disorder (ADHD) tipe ringan dalam proses pemerolehan bahasa kedua (SLA). Fokus utama penelitian ini adalah mengidentifikasi bagaimana hambatan fungsi eksekutif, khususnya dalam hal atensi berkelanjutan (sustained attention) dan memori kerja (working memory), memengaruhi kelancaran berbahasa. Menggunakan pendekatan kualitatif melalui studi kasus dan analisis tugas (task analysis), penelitian ini mengamati interaksi pembelajar saat menghadapi teks kompleks dan tugas komunikatif.Temuan awal menunjukkan bahwa pembelajar dengan ADHD ringan secara tidak sadar mengembangkan mekanisme kompensasi yang unik, seperti penggunaan alat bantu visual yang intensif, pemecahan tugas menjadi unit-unit mikro (micro-tasking), serta pemanfaatan teknologi kecerdasan buatan (AI) sebagai pengatur kognitif eksternal. Namun, strategi ini sering kali berbenturan dengan metode pengajaran bahasa tradisional yang bersifat linear. Analisis kritis dalam penelitian ini menekankan pentingnya instruksi berdiferensiasi dan pendekatan berbasis tugas (Task-Based Language Teaching) yang lebih fleksibel. Hasil penelitian ini diharapkan dapat memberikan kontribusi pada pengembangan silabus yang lebih inklusif dan ramah neurodiversitas, serta memberikan panduan praktis bagi pengajar bahasa dalam memfasilitasi strategi belajar yang mandiri dan efektif bagi pembelajar dewasa dengan tantangan atensi.